CREDIT RISK MEASURMENT IN ISLAMIC BANKING” A Case Study of Dubai Islamic Bank and Abu Dhabi Islamic Bank during the period (2008-2012) - MECHERI, FARID; ATROUS, SABRINA (مجلة الاقتصاديات المالية البنكية وإدارة الأعمال; No 05 (2018): مجلة الاقتصاديات المالية البنكية و إدارة الأعمال, 2018)
Abstract : The aim of this study is to identify and measure the credit risk that Islamic banks may face. We selected two Islamic banks, Dubai Islamic Bank and Abu Dhabi Islamic Bank, as a sample of the study during the period 2008-2012. We focused on several aspects of these risks and studied nature and then mentioned some practices and measures used by these banks and in line with the principles of Islamic law to address these risks and management and to mitigate their effects. Keywords:  Credit risk, Islamic banks, Credit risk measurement. الملخص : الهدف من هذه الدراسة هو معرفة وقياس مخاطر الائتمان التي قد تواجه البنوك الإسلامية، لذلك اخترنا اثنين من البنوك الإسلامية هما: بنك دبي الإسلامي وبنك أبوظبي الإسلامي كعينة للدراسة وذلك خلال الفترة (2008-2012)، حيث ركزنا على عدة جوانب تتعلق بهذه المخاطر ودرسنا طبيعتها ثم ذكرنا بعض الممارسات والتدابير التي يستخدمها هذين البنكين والتي تتماشى مع مبادئ الشريعة الإسلامية  لمواجهة هذه المخاطر وإدارتها وكذا للتخفيف من آثارها. الكلمات المفتاحية: مخاطر الائتمان، المصارف الإسلامية، قياس مخاطر الائتمان